Technology of Post-Institutional Support to Exiters of State-Run Institutions for Orphans in the Process of Obtaining Professional Education and Primary Employment - Oslon V.N; Celenina E.V (Moscow State University of Psychology and Education, 2018)
The article presents proprietary technology of post-institutional support to exiters of state-run institutions for orphans in the process of obtaining professional education and primary employment. This technology was successfully tested in the RF regions in 2017. The Russian Ministry of Education and Science recommends technology for implementation in the federation. The methodological prerequisites for the technology are the ecological-dynamic and resource approaches, the empirical foundations are the studies' results on the exiters' post care outcomes, done from 2006 to 2017, and the generalization of corresponding practices in RF. The technology is aimed at optimizing the organizational and managerial process of post-gradual support to exiters in the continuum of their receiving vocational education and primary employment. The peculiarity of the technology lies in the fact that it is regional and is implemented at two levels: at the level of organizations directly working with graduates regardless of the form of ownership, as well as at the level of the executive power and the local community. This technology allows to systematize the support activities provided to this category of young people in the period of professional self-determination and development.